(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Media in India is mostly self-regulated. The existing bodies for regulation of media such asthe Press Council of India which is a statutory body and the News Broadcasting Standards Authority, aself-regulatory organization, issue standards which are more in the nature of guidelines. The mediaperforms a decisive part in unveiling of a fact and awaking the general public but recently variouscircumstances have surfaced some apprehension on its dependability. In the traditional mass media,ethical practices have been an ancillary to it but with the advancement in technology, these definitepractices are subject to constant challenge. This essay tries to put light on those aberrations andascertain the moral principles of the media that has been manoeuvred for a physical objective. Theauthor asserts that the modern perspective of holding the responsibility of regulation with the mediamay result in exploitation of this power for its own business profits. Thus, the essay aims at bringing outan analysis of how media can be regulated in India.Justice Leveson’ inquiry has triggered the discussions in media ethical practices in Britain as well asother countries. Thus, the essay analyses the effect of the inquiry in India with other counterparts. Theessay aims to appraise the measures to solve all conflicts concerning to the regulation of the media inthe backdrop of the Leveson inquiry and provide some suggestions for its betterment.